Prevalence of Obesity and Dental Caries in High School Adolescents during the First Decade of Saudi Vision 2030: A Cross-Sectional Study - Deema J. Farsi; Nada J. Farsi; Heba M. Elkhodary; Logain K. Alattas; Ali B. Alshaikh; Najat M. Farsi (MDPI AG, 2024)
Saudi Vision 2030 was launched in 2016. Obesity and dental caries are both highly prevalent in Saudi adolescents and have been targeted by the Vision's health initiatives. The aim is to assess their prevalence in adolescents during the first decade since the launch of the Vision. This cross-sectional study was conducted in Jeddah, Saudi Arabia using a stratified sample of 571 high school students, with an average age of 16.7 (0.6). Their height and weight were measured, and their body mass index (BMI) was calculated. The decayed, missed, and filled scores (DMFTs) were recorded after an oral examination. Non-parametric tests were used to assess the associations of DMFT with BMI, sex, and school type; and its predictors were assessed. One-third of males were overweight/obese compared with 22% of females. Males exhibited higher DMFTs than females. DMFTs were higher among public school students than among their private school counterparts. No significant association was observed between DMFT and BMI. Sex and school type were significant predictors of DMFT. The prevalence of obesity has slowly decreased in adolescents, but the prevalence of dental caries has not. There was no significant relationship between these conditions. Saudi Vision 2030's current preventive/educational initiatives may be more effective in combating obesity than dental caries.